Manajemen Beternak Kambing Perah pada Komunitas Ternak Kambing Perah Penerima Hibah UPZ BAZNAS PT Semen Padang - Riesi Sriagtula; Qurrata Aini; Mardhiyetti Aini; Febryon Tri Intano (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
The Etawa Dairy Goat Farming Program is one of the Economic Sector programs of UPZ BAZNAS PT Semen Padang by distributing a grant of 42 Etawa crossbred goats (ECG) to seven underprivileged Heads of Families (KK). UPZ BAZNAS PT Semen Padang chose dairy goats because they have high economic potential. Challenges in raising dairy goats include feed management, livestock health, and poor maintenance techniques. The dairy goat maintenance system in the community is traditional. Poor feed quality impacts production, reproduction, and livestock health. To make the dairy goat grant effective, assistance is needed to guide farmers on feed, health, and maintenance so that goat farming can benefit farmers and become a family business unit. The Faculty of Animal Science Service Team and students of the Animal Science Study Program at Universitas Andalas carry out community service activities from July to November 2024. The community service activities method includes surveys, counseling, and activity evaluation. After the community service activities, improvements were seen in feed management, and farmers became skilled at handling scabies in livestock. Based on the community service activities that have been carried out, it can be concluded that farmers' knowledge about dairy goat maintenance management has increased. Farmers are skilled at treating scabies with traditional medicine because it is effective and more economical.